Analisis Faktor-Faktor yang Mempengaruhi Akuntan Beregister Berprofesi Sebagai Akuntan Publik - Salmiah, Neneng; Afriany, Arista Natia (AKMENIKA, 2017)
This research aimed at empirically testing of the factors that affect the registered accountant as members of IAI in Pekanbaru worked as a public accountant that focused to test the effect of the USAP cost, USAP process and occupational risk with variable electoral career as a public accountant. USAP cost, USAP process and occupational risk variables are as independent variables, associated with various assumptions. This research had 45 samples and used purposive sampling as the technique. Located on Pekanbaru area and using primary data. The data method is by spreading some questionnaires. Measurements of variables performed with Likert scale. Data analysis was conducted through quantitative analysis. Quantitative data analysis was performed by multiple regression analysis and hypothesis testing was done by t-test. The results obtained show that the USAP process and occupational risk significantly influence the selection of a career as a public accountant, USAP cost influence on elections as a public accounting career, but the effect is not significant. Overall USAP cost, USAP process and occupational risk jointly significant effect on elections to the selection of a career as a public accountant.